Cytofluorimetric and immunohistochemical comparison for detecting bone marrow infiltration in non-Hodgkin lymphomas: a study of 354 patients. (January 2020) - Statuto, Teodora; Valvano, Luciana; Calice, Giovanni; Villani, Oreste; Pietrantuono, Giuseppe; Mansueto, Giovanna; D'Arena, Giovanni; Vita, Giulia; Lalinga, Vittoria; Possidente, Luciana; Del Vecchio, Luigi; D'Auria, Fiorella; et al.
Highlights: FC and IHC were compared for detecting the infiltration in BM of patients with NHL. Discrepancy between the two methods was found in 14 % of cases examined. 9.3 % of total population (354 patients) was BMA/FC + BMB/IHC-. 4.5 % was BMA/FC- IHC+/BMB. FC of BMA may be of diagnostic help in selected cases of NHL. Abstract: Morphological and immunohistochemical (IHC) analysis of bone marrow biopsies (BMB) is routinely performed during staging of patients with non-Hodgkin's lymphoma (NHL). Aiming to evaluate the possible diagnostic value of flow cytometry (FC) on bone marrow aspirates (BMA), as compared with BMB, we retrospectively reviewed BMA specimen of 354 NHL. In 305 cases (86.1 %), there was a concordance between the two investigations. A discordance was detected in 49 cases (14 %): in 33 of these (9.3 % of total population), FC analysis of BMA was positive, whereas BMB, supported by IHC, was negative; in 16 (4.5 % of total population), FC did not detected lymphoid infiltration, while BMB was positive. Although the clinical implications of such an observation remain unclear, we think our results may be useful in the context of current staging procedures, also opening a possible future perspective in the setting of minimal measurable disease in these patients.